The Need for a More Robust Education Studies: The Impact of Mediation and Moderation Variables for Deeper Insights - Oji, John; Alordiah, Caroline Ochuko (NIU Journal of Educational Research, 2024)
Incorporating mediation and moderation variables into education studies has theoretical and empirical ramifications that this study intends to investigate. A foundation for comprehending the intricate links and mechanisms influencing educational outcomes is offered by this research. To determine the essential ideas and elements associated with mediation and moderation, a comprehensive analysis of pertinent literature and research studies in the field of education was carried out. A thorough model that demonstrates how mediation and moderation variables can be incorporated into education studies was created based on this investigation. In elucidating the links between diverse educational characteristics, the research emphasises the importance of mediation and moderation. It illustrates how some variables influence the relationship between independent and dependent variables by acting as mediators, and how other variables influence the degree or direction of these associations by acting as moderators. A more comprehensive understanding of the underlying mechanisms and contextual factors influencing educational outcomes is provided by the inclusion of mediation and moderation variables in education studies. Through the integration of various variables into an all-encompassing model, scholars can acquire a more profound understanding of the intricate dynamics involved in educational processes and results. Policymakers and educators should consider the practical ramifications of implementing the suggested model. By focusing on these aspects, policies and interventions can be created that will improve teaching methods and raise student achievement. Keywords: Mediation, moderation, education studies, Methodological challenges, Measurement limitations, Statistical techniques.